2021
DOI: 10.14202/vetworld.2021.492-498
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic lumbosacral vertebral abnormalities and constipation in cats

Abstract: Background and Aim: Lumbosacral intervertebral disk disease (IVDD) in cats usually develops concurrent with constipation, spondylosis deformans, and sacralization. However, the prevalence of lumbar IVDD in cats was considered low, and there was less information on the incidence of non-traumatic lumbosacral vertebral abnormalities that may affect large bowel dysfunction. This study aimed to retrospectively investigate the relationship between non-traumatic lumbosacral vertebral abnormalities, both congenital an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The investigations of Thanaboonnipat et al. (2021) in 1 365 cats revealed the following congenital anomalies: six lumbar vertebrae (141), sacralisation (48), lumbarisation (16), hemivertebrae (1), and five lumbar vertebrae (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigations of Thanaboonnipat et al. (2021) in 1 365 cats revealed the following congenital anomalies: six lumbar vertebrae (141), sacralisation (48), lumbarisation (16), hemivertebrae (1), and five lumbar vertebrae (1).…”
Section: Discussionmentioning
confidence: 99%
“…Even if the number of animals is higher, the percentage of LTV (sacralisation + lumbarisation) in their study corresponds to those of our findings. Thanaboonnipat et al. (2021) concluded that cats with abnormal lumbosacral vertebrae are prone to having more problems with the large bowel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the number of animals was higher, the percentage of lumbosacral transitional vertebra (sacralisation+lumbarisation) in this study was appropriate to that of our findings. It has been concluded, that cats with abnormal lumbosacral vertebrae are predisposed to have more problems with the large bowel [43].…”
Section: Discussionmentioning
confidence: 99%
“…Constipation in cats is a temporary loss of significant bowel function brought on by various issues, with no preference for age, sex, or breed. Constipation can cause irregular fecal contents, such as small, spherical, or ribbon-like feces, difficulty defecating, atypical defecation, abdominal swelling, tenesmus, and infrequent defecation (Thanaboonnipat et al, 2021). Constipation can occur due to several reasons, such as refusal to defecate due to inability to posture to defecate, orthopedic problems, or neurologic problems (Thompson, 2014).…”
Section: Introductionmentioning
confidence: 99%